Towards understanding latrophilin signalling in C.elegans - Al-Harbi, Hamad (2010)
Latrophilin (LAT-1) is a G -protein-coupled receptor (GPCR), and mediates Black widow spider venom toxicity (Mee et al., 2004). A deletion in the lat-1(ok1465) gene (allele ok1465) in C. elegans causes 97% of worms to die during embryogenesis or early larval stages (Adenle, 2008). Thus latrophilin has an essential function in development, but it is not known how latrophilin signalling causes biological effects. The aim of this study is to identify genes that mitigate the effect of the lat-1(ok1465) deletion allele on offspring lethality, with a view to identifying the pathways involved in latrophilin signalling that mediate developmental lethality.